InOnAt time travel adventure - Ong, Elly; Ahmad, Muhammad Khairul; Abdul Rani, Muhd Syahir; Mohd Noor, Nazirul Mubin; Mohd Salim, Mohamad Safwat Ashahri (2025)
Learning English prepositions of time using a tenses-themed board game is fun and exciting. The use of a board game promotes involvement and evaluation in learning English prepositions of time through challenges, incentives, and collaboration. Students often face difficulties in utilizing prepositions of time across various tenses. Past studies show that board games promote students' mastery of English grammar, especially prepositions of time, hence increasing the fun and context-dependent importance of language application. The "InOnAt Time Travel Adventure" board game was created to facilitate students' mastery of prepositions of time through repetition, immersive environments, and engaging, motivational, and memorable activities on past, present, and future tenses. A survey was administered to 53 third-semester diploma students selected for the study before and after a two-week grammar class to assess the effectiveness of a board game in assisting students’ learning of prepositions of time. The results show that the "InOnAt Time Travel Adventure" significantly enhanced students' capacity to independently comprehend the designated grammar topic. The board game can be economically made and used, so it ought to be acknowledged as a helpful tool for individuals learning the English language. It is recommended that there should be an investigation of the impact of board games designed for the long-term mastery of prepositions of time, together with the performance of students from various faculties and cohorts.